News coverage, exposure, knowledge, attitude, and behavior of Pakistani and Malaysian students towards sexual harassment reports in newspapers - Hilal, Fatima Syeda (2020)
Sexual harassment (SH) is not a new issue in Malaysia and Pakistan. There has been no comprehensive investigation on SH reported in the national dailies of both countries in terms of level of knowledge, attitudes, and behavior. The present study was conducted on the basis of content analysis, examining SH news coverage published in Berita Harian daily of Malaysia and Daily Jang of Pakistan to identify the patterns of SH news coverage. A total of 382 and 384 university students from Malaysia and Pakistan respectively, voluntarily participated in a self-administered survey. The survey was carried out following approval from the respective universities' Research Ethic Committees. The survey examined SH news exposures, levels of SH knowledge, degrees of intolerant attitudes toward SH, and propensity to act against SH among university students in both countries. Knowledge, attitudes and practices (KAP) and Cultivation Theories, were applied in the study for assessing patterns of coverage. At the conclusion of the study, results showed that both Berita Harian and Daily Jang did not elevate awareness on SH among the survey respondents. SH news in Daily Jang were not prominent, and had no thematic frame or negative direction. Berita Harian had less than 50% SH coverage with thematic frames set in positive direction but had no prominence. The majority of the respondents from both countries had moderate levels of SH news exposure, knowledge, intolerant attitudes toward SH, and propensity to act against SH. Regression analyses on Pakistani respondents revealed that SH news exposure had no significant relationship with intolerant attitude toward SH and the propensity to act against SH but recorded a significant positive relationship with SH knowledge. SH knowledge, in turn, had significant relationships with intolerant attitudes toward SH and propensity to act against SH. The Malaysian respondents revealed that SH news exposure had significant positive relationship with SH knowledge. The results also showed significant relationship with intolerant attitudes towards SH. The present study provided insights into similarities and differences in the nature of coverage on SH in Malaysia and Pakistan. The study suggested that high exposure to news, high level of knowledge, right attitudes and behavior with respect to SH have yet to become a norm in Malaysian and Pakistani societies. The relationships between knowledge, attitudes and behavior variables appeared to be dependent on the societies' culture.